Sosialisasi Penyusunan Naskah Akademik Rancangan Peraturan Daerah Inisiatif DPRD Provinsi Sumatera Utara Tahun 2025 tentang Tanggung Jawab Sosial dan Lingkungan Perusahaan (TJSLP) - Mhd. Ansor Lubis; Azwir Agus; Muslim Harahap; Gerald Elisa Munthe; Sugih Ayu Pratitis; Dearma Sinaga; H. Abdul Lawali Hasibuan (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2026)
Corporate Social and Environmental Responsibility (CSER) plays a strategic role in supporting sustainable development through improving community welfare and environmental protection. However, the implementation of CSER in regional areas still faces several challenges, including the lack of optimal local regulations, weak coordination among stakeholders, and limited understanding among the public and business actors regarding CSER implementation. This community service activity aims to provide socialization regarding the preparation of the Academic Draft for the Regional Regulation Initiative of the Regional House of Representatives (DPRD) of North Sumatra Province in 2025 concerning CSER. The activity was carried out through lectures, interactive discussions, and academic assistance involving local government representatives, academics, business sectors, and the community. The results of the activity indicated an increased understanding among participants regarding the importance of establishing the CSER Regional Regulation Draft, the mechanism for preparing academic manuscripts, and the need for collaboration between the government, companies, and the community in supporting participatory and sustainable regional regulations.